Fashion: Akumulasi Modal dan Habituasi Pada Praktik Dakwah Komunitas Hijrah - Wisnu Pudji Pawestri; Siti Kholifah (UIN Sunan Gunung Djati Bandung, 2020)
The diversity of religious practices forms a new pattern, where each community is challenged to be 'in tune' with the current trend and situation. The pattern challenges each community to compete with others to provide good bargaining power so the audience is in the discourse that they produced. To propagate hijrah discourse, Taubah Muslim (Community’s name is disguised) community uses fashion as a strategy in da’wah activism. Taubah Muslim hijrah community is a community that persuades millennials to hijrah through da'wah. Fashion in this context is positioned as a medium as well as a 'new way' to approach the da'wah target. This article puts fashion as a social practice in which there are forms of representation and expression of Islamic values. Using a descriptive qualitative method, this article highlights how fashion is used and chosen by agents in da’wah arena as a strategy to reproduce hijrah discourse. Based on Pierre Bourdieu's social practice theory, the results of the analysis conclude that fashion is used as a placement strategy to encourage perceptions of shared identity. Furthermore, fashion functionally is used as an acculturation technique to approach the da'wah target (young generation). The choice of fashion as a da'wah strategy is based on habitus and capital owned by agents in the da'wah arena. Then, Fashion is treated as a representation of other meanings that are presented by agents to create reality, which is based on their habitus and capital. The existence of capital becomes an important thing for the community to maintain, strengthen, and differentiate (distinction) with others in achieving a dominant position, namely in terms of propagative hijrah discourse